Fe-biochar as a safe and efficient catalyst to activate peracetic acid for the removal of the acid orange dye from water. (November 2022) - Shi, Changjie; Wang, Yong; Zhang, Kai; Lichtfouse, Eric; Li, Cong; Zhang, Yunshu
Abstract: Pollution of wastewater and natural waters by organic contaminants is a major health issue, yet actual remediation methods are limited by incomplete removal of recalcitrant contaminants and by secondary pollution by chlorinated contaminants and catalytic metals. To attempt to solve these issues, we tested the removal of acid orange by peracetic acid (PAA), a safe oxidant, activated by Fe-biochar that iron anchored on biochar to prevent secondary pollution by iron. Fe-biochar was synthesized using a simple, one-step pyrolysis method. We investigated the effects of PAA concentration, pH, humic acids, chloride, bicarbonate on the reaction. Radical quenching and electron paramagnetic resonance were used to identify reacting species. Results showed that the granulous structure of Fe-biochar and the presence of Fe, Fe3 O4, Fe2 O3, and Fe3 C on Fe-biochar surface. The highest removal of acid orange of 99.9% was obtained with 1.144 mM PAA and 0.3 g/L Fe-biochar at pH 7. Acid orange removal increases with Fe-biochar dose, decreases with pH, is slightly inhibited by humic acids and bicarbonate, and is not modified by chloride. Our experimental results suggested that CH3 C(O)OO· and CH3 C(O)O· are the main radical species, but there may also be non-radical effects in Fe-biochar/PAA process. Fe-biochar displayed high re-usability, with 92.8% removal after five uses. Graphical abstract: Image 1 Highlights: The mechanism of the Fe-biochar/PAA process was investigated by removing acid orange. CH3 C(O)O· and CH3 C(O)OO· act as the primary radicals. There may also be non-radical effects in the process of acid orange removal. Fe-biochar has a high recycling rate in the Fe-biochar/PAA process.